2007
DOI: 10.1090/s0002-9947-07-04116-5
|View full text |Cite
|
Sign up to set email alerts
|

Finite generation of symmetric ideals

Abstract: Abstract. Let A be a commutative Noetherian ring, and let R = A[X] be the polynomial ring in an infinite collection X of indeterminates over A. Let S X be the group of permutations of X. The group S X acts on R in a natural way, and this in turn gives R the structure of a left module over the group ring R[S X ]. We prove that all ideals of R invariant under the action of S X are finitely generated as R[S X ]-modules. The proof involves introducing a certain well-quasi-ordering on monomials and developing a the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
136
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(137 citation statements)
references
References 17 publications
1
136
0
Order By: Relevance
“…In proving the Noetherianity of R, it was shown that a symmetric ideal I has a special, finite set of generators called a minimal Gröbner basis. However, the more basic question of whether I is always cyclic (already asked by Josef Schicho [4]) was left unanswered in [1]. Our result addresses a generalization of this important issue.…”
mentioning
confidence: 62%
See 2 more Smart Citations
“…In proving the Noetherianity of R, it was shown that a symmetric ideal I has a special, finite set of generators called a minimal Gröbner basis. However, the more basic question of whether I is always cyclic (already asked by Josef Schicho [4]) was left unanswered in [1]. Our result addresses a generalization of this important issue.…”
mentioning
confidence: 62%
“…. }, although as remarked in [1], this is not really a restriction. In this case, S X is naturally identified with S ∞ , the permutations of the positive integers, and…”
Section: Theorem 1 For Every Positive Integer N There Are Symmetricmentioning
confidence: 91%
See 1 more Smart Citation
“…For n = 1 this theorem was proved by Cohen [3] in 1967 and rediscovered independently by Aschenbrenner and Hillar [1] in 2007; for an arbitrary positive n this was proved by Cohen [4] in 1987 and rediscovered independently by Hillar and Sullivant [13] in 2012. Cohen's results were motivated by the finite basis problem for identities of metabelian groups and the results of Aschenbrenner, Hillar and Sullivant by applications to chemistry and algebraic statistics.…”
Section: Introductionmentioning
confidence: 95%
“…The following theorem was proved by Draisma [6] in 2010; it solves a problem arising from applications to algebraic statistics and chemistry posed in [1].…”
Section: Introductionmentioning
confidence: 99%